A Domestic Investigation of Online Banking - Varga, Dóra; Kiss, Virág (International Journal of Engineering and Management Sciences, 2023)
Nowadays, the spread of digitalization is constantly increasing. The current rising generation is already a “digital native”. As part of digitalisation, mention should be made of the Internet, which has been given a prominent role in our daily lives. We search for information on the Internet, we communicate, we buy. Due to these factors and the pandemic in 2020, internet administration has become a priority. Banks need to constantly adapt to meet their needs, promoting convenient, home banking. In the course of our research, we focused on this continuous adaptation and the resulting improvements. The research focused on the Internet and mobile banks of large Hungarian banks. Sampling took place over 2 periods. Among the primary research tools, we chose document analysis, and netnography. In the research, we compared the functions available on the platforms, the consumer perception of mobile banks and other variables. Based on the results obtained during the research, it can be stated that domestic banks are constantly developing their application along different trends and trying to adapt to changing needs. Serious changes had to be made in the mobile banks of most large banks, even with the permanent elimination of their former mobile banks. Changes can have a strong impact on consumers, who are often more likely to have a negative view of them. Digitalisation is also particularly important in this sector. The study contains the details of the course work prepared for the Scientific Students’ Associations Conference.